Risk factors for incident HIV infection among antenatal mothers in rural Eastern Cape, South Africa - Charles Bitamazire Businge; Benjamin Longo-Mbenza; Verona Mathews (Taylor & Francis Group, 2016)
Background: The prevalence of HIV among antenatal clients in South Africa has remained at a very high rate of about 29% despite substantial decline in several sub-Saharan countries. There is a paucity of data on risk factors for incident HIV infection among antenatal mothers and women within the reproductive age bracket in local settings in the Eastern Cape, South Africa. Objective: To establish the risk factors for incident HIV infection among antenatal clients aged 18-49 years attending public antenatal clinics in rural Eastern Cape, South Africa. Design: This was an unmatched case-control study carried out in public health antenatal clinics of King Sabata District Municipality between January and March 2014. The cases comprised 100 clients with recent HIV infection; the controls were 200 HIV-negative antenatal clients. Socio-demographic, sexual, and behavioral data were collected using interviewer-administered questionnaires adapted from the standard DHS5 women's questionnaire. Multivariate logistic regression models were used to identify the independent risk factors for HIV infection. A p<0.05 was considered statistically significant. Results: The independent risk factors for incident HIV infection were economic dependence on the partner, having older male partners especially among women aged ≤20 years, and sex under the influence of alcohol. Conclusions: Therefore, effective prevention of HIV among antenatal mothers in KSDM must target the improvement of the economic status of women, thereby reducing economic dependence on their sexual partners; address the prevalent phenomenon of cross-generation sex among women aged <20 years; and regulate the brewing, marketing, and consumption of alcohol.